The influence of farm resources and management decisions on the severity of Striga infestation and maize productivity in western Kenya - Rusinamhodzi, L.; Nguyen, E.; Marrou, H.; Uzamushaka, S.; Corbeels, M. (Wiley, 2025)
The control of Striga is of critical importance for smallholder farmers cultivating maize and other cereals in the western region of Kenya. Therefore, advanced knowledge and analysis is needed to understand farmers' resource endowment and decision making with regards to crop management, and the possible effect on Striga infestation and crop productivity. The overall objective of the study was to understand the role of resource endowment and allocation decisions on Striga infestation and maize productivity and offer effective and locally adapted options in western Kenya. The study used semi-structured questionnaires, focus group discussions and resource flow mapping to identify farm resources and key management decisions that are critical in management of Striga on smallholder farms. Soil was sampled from fields of selected farms and taken to the laboratory for analysis including Striga seed counts. In the fields, Striga shoots counts, and maize yield were recorded. Socio-economic variables such as land size, household income, labour availability, were used to construct a farm typology and assign farmers to different resource groups (RGs). Our results showed that household diversity leads to different land-use patterns, resource-use intensity and agricultural management practices which affect soil fertility and Striga infestation. Poor-resourced farmers tend to be associated with poor crop and soil management which results in maize fields with low soil fertility and high level of Striga infestation. Soil organic carbon showed a strong negative association with Striga infestation. Improving soil fertility is, therefore, the central component of any integrated and sustainable Striga management approaches, and technological solutions to address Striga and soil fertility issues, and they must be tailored to the farm and field diversity. The inclusion of legumes is highly recommended either as rotation or intercropping depending on land availability. Where possible, farmers may use mulch from previous crop residues to suppress weed emergence and prevent flowering and seed setting. Hand weeding though tiresome, remains a low-cost effective method to control Striga especially in areas where fields are small as in western Kenya.